African Mobility and Labor in Global History. Issue 3 (4th March 2016) - Callebert, Ralph
Abstract: Popular discourses on globalization and many global histories do not have much to say about Africa, despite significant advances in global history's engagements with Africa in recent decades. The continent generally only features to the extent that it trades, usually as subordinate partner, with the rest of the world or is penetrated by foreign merchants and colonizers. Such accounts approach the continent's integration into world markets from without . This literature thus emphasizes colonial transport infrastructure, export trade, and forms of labor that feed directly into global markets, including wage labor and cash cropping. The historiography on African mobility and labor, however, opens up promising avenues for better integrating the continent into global history. African historians' growing focus on local mobility and informal trade, on the ways in which Africans took part in shaping connections with global markets, and on productive activities not geared towards export allows us to reframe Africa in global history as more than a passive victim of colonialism, the slave trade, or global capital.